Successful weight loss maintenance includes long-term increased meal responses of GLP-1 and PYY3–36. Issue 6 (June 2016) - Iepsen, Eva W; Lundgren, Julie; Holst, Jens J; Madsbad, Sten; Torekov, Signe S
Abstract : Objective: The hormones glucagon-like peptide 1 (GLP-1), peptide YY3-36 (PYY3–36 ), ghrelin, glucose-dependent insulinotropic polypeptide (GIP) and glucagon have all been implicated in the pathogenesis of obesity. However, it is unknown whether they exhibit adaptive changes with respect to postprandial secretion to a sustained weight loss. Design: The study was designed as a longitudinal prospective intervention study with data obtained at baseline, after 8 weeks of weight loss and 1 year after weight loss. Methods: Twenty healthy obese individuals obtained a 13% weight loss by adhering to an 8-week very low-calorie diet (800kcal/day). After weight loss, participants entered a 52-week weight maintenance protocol. Plasma levels of GLP-1, PYY3–36, ghrelin, GIP and glucagon during a 600-kcal meal were measured before weight loss, after weight loss and after 1 year of weight maintenance. Area under the curve (AUC) was calculated as total AUC (tAUC) and incremental AUC (iAUC). Results: Weight loss was successfully maintained for 52 weeks. iAUC for GLP-1 increased by 44% after weight loss ( P <0.04) and increased to 72% at week 52 ( P =0.0001). iAUC for PYY3–36 increased by 74% after weight loss ( P <0.0001) and by 36% at week 52 ( P =0.02). tAUC for ghrelin increased by 23% after weight loss ( P <0.0001), but at week 52, the increase was reduced to 16% compared with before weight loss ( P =0.005). iAUC for GIP increased by 36% after weight loss ( P =0.001), but returned to before weight loss levels at week 52. Glucagon levels were unaffected by weight loss. Conclusions: Meal responses of GLP-1 and PYY3–36 remained increased 1 year after weight maintenance, whereas ghrelin and GIP reverted toward before-weight loss values. Thus, an increase in appetite inhibitory mechanisms and a partly decrease in appetite-stimulating mechanisms appear to contribute to successful long-term weight loss maintenance.